High resolution fourier transform spectrum of PD3 in the regionof the stretching overtone bands 2ν1 and ν1 + ν3 - Ulenekov (Ulenikov) O. N. Oleg Nikolaevich; Onopenko G. A.; Yukhnik (Yuhnik) Yu. B. Yuliya Borisovna; Bekhtereva E. S.; Tyabaeva N. E.; Bürger H.; Jerzembeck W.; Fusina L. (2003, 2003)
В фонде НТБ ТПУ отсутствует